Factors Affecting Handwashing Behavior in Students of Satria Binjai Private Senior High School in 2022 - Erin Efrina; Nur'aini Nur'aini; Aida Fitria (International Journal on Advanced Science, Education, and Religion, 2023)
Health is a basic right of every human being and is one of the factors that determine the quality of Human Resources (HR). Therefore, health needs to be maintained and improved in quality and protected from threats that harm it. As for efforts to improve health status, namely by maintaining a lifestyle, eating patterns and preventing disease through hand washing behavior.The method of research is an analytic survey with a cross sectional design. The research location is at the Satria Binjai Private High School. The population in this study were 128 students of Satria Binjai Private High School class X andXI. The sample in this study were all students of class X and XI as many as 128 people and the sampling technique used the total population technique, namely the entire population was sampled. Techniques and methods of collecting data using a questionnaire.From the results of the logistic regression test analysis, it was found that the variable that had an influence on hand washing behavior was the knowledge variable, p value = 0.001, the facilities variable, p value = 0.003, the parental role variable, p value = 0.019, the role variable for health workers. obtained p value = 0,038, peer role variable obtained p value = 0,000. The significant variable that has an influence on hand washing behavior in Satria Binjai Private High School students in 2022 are the knowledge and the role of peers.The conclusion in this study is that in carrying out hand washing behavior is influenced by factors of knowledge, facilities, the role of parents, the role of health workers, and the role of peers. So it can be suggested that parents, health workers & friends can support Satria Binjai Private High School students to carry out hand washing behavior and increase the knowledge of Satria Binjai Private High School students about the importance of hand washing behavior.